Eponimy w edukacji językowo-kulturowej cudzoziemców uczących się polszczyzny - Graf, Magdalena; Nowak-Pasterska, Ewa (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The subject of the discussion is the characteristics of the structure and meaning of eponyms and their importance in the glottodidactic process. The authors indicate the most important research proposals and problems that result from the borderline character of these lexemes, situated between proper names and appellative lexis. Eponyms as words derived from proper names, created in the process of apellativisation can also serve as an important source of cultural information. Therefore, they may be an interesting source of their introduction at various levels of the didactics of Polish as a foreign language; however, a review of the available textbooks leads to the conclusion that eponymic lexis is scarcely present in the didactics of Polish as a foreign or second language. The authors reflect on the reason for this absence, while showing the didactic potential of eponyms.